Mendelian randomization analysis does not reveal a causal influence between keratoconus and three major mental disorders - Zhang, Xueyan; Wang, Qiaoling; Cui, Fenghua; Wu, Xuelian; Zhang, Chenming (Frontiers in Psychiatry, 2024)
Background Observational studies have suggested at a possible link between keratoconus (KC) and various mental disorders, but the exact direction of causation in these associations remains unclear. This study aims to investigate the potential causal link between KC and three prominent mental conditions: Anxiety, Depression, and Schizophrenia. Methods Using instrumental variables identified from Genome-wide association study (GWAS) data of European individuals, we conducted bidirectional two-sample Mendelian Randomization (MR) analyses to explore potential causal relationships between KC and the three major mental disorders. We primarily employed the Inverse-Variance Weighted (IVW) method to evaluate causality. In addition, we performed four supplementary MR methods (MR-Egger, Weighted Median, Simple Mode, and Weighted Mode). Furthermore, we conducted various sensitivity analyses to assess heterogeneity, horizontal pleiotropy, and result stability. Results Our findings did not reveal any concrete evidence of a causal link between KC and the three major mental disorders, namely anxiety, depression, and schizophrenia [anxiety: odds ratio (OR)=0.997, 95% confidence interval (CI)=0.988–1.008, p = 0.621; depression: OR=1.008, 95% CI=0.999–1.017, p = 0.084; schizophrenia: OR=1.002, 95% CI= 0.984–1.020, p = 0.840]. Similarly, the three major mental disorders were not caustically associated with KC [anxiety: OR=1.014, 95% CI=0.635–1.620, p = 0.953; depression: OR=1.109, 95% CI= 0.749–1.643, p = 0.604; schizophrenia: OR= 0.969, 95% CI= 0.884–1.062, p = 0.497]. The sensitivity analyses indicated that the results remained robust, with no signs of pleiotropy or heterogeneity. Conclusions Our study does not support a genetically determined significant causal connection between KC and the three major mental disorders. The increased occurrence of mental disorders observed in KC patients in observational reports likely arises from factors that can be modified. Further research is warranted to unveil the underlying mechanisms behind the associations observed in observational studies.